How does handwriting of letters affect mirror-image discrimination? - Corbal, Maria Luísa da Silva (2018)
We explored whether training motor actions that match letter motor representations, supposedly supported by the dorsal visual stream, would contribute to mirror-image discrimination in tasks supported by the ventral visual stream, especially of letters for which orientation is the only feature that can assist discrimination, i.e., reversible letters. Two groups of preliterate children trained motor actions during 20, 20-min daily sessions, in tablet games developed specifically for this study following human-computer interaction principles. Six children played the draw game, tracing and copying letters, and five children played the contact game (the control game) by moving the letters from an initial to a target point. Two reversible letters (d; p), two non-reversible (e; k), and two symmetrical letters (o; x) were used in both games. To evaluate the impact of motor training on orientation processing, children performed independent tasks before and after the training: a four-alternative forced-choice task with letters, and same-different matching tasks with letters and geometric shapes. Children’s performance in the games suggests that letter motor representations have emerged but only when the trained motor actions matched the letter shape (i.e., in the draw game) and they were more important for reversible than for non-reversible or symmetrical letters. The difficulty in mirror-image discrimination found in the four-alternative forced-choice task provide an original contribution showing that this difficulty is not specifically due to the working memory demands of the tasks in which it occurs. The results in the same-different tasks suggest that children became more sensitive to plane-rotation contrasts because in both games they had contact with letters differing by that contrast (i.e., d-p). Finally, when we compared both groups’ performance in the independent tasks before and after the training, no significant differences were found. Therefore we could not confirm, or refute, the importance of training motor actions that match letter motor representations on mirror-image discrimination.